THE EFFECTIVENESS OF FANTASY STORIES TECHNIQUE TOWARDS STUDENTS’ CREATIVITY IN WRITING - Ujang Supriadi (Journal of Languages and Language Teaching, 2016)
This research is aimed to find out whether or not using Fantasy Stories Technique  Toward Students’ Creativity in Writing is effective. The research was experimental research and the design used was used one group pre-test  post-test design. The population of the study was the second grade students of SMA Negeri 1 Praya Timur which consisted of only one class with 25 students’. So, the researcher took all the number of population as the sample. The data were collected by using pre-test and post-test. The instrument of this research used was writing test. The technique that was used to analyse the data was t-test formula. From the data analysis, it was found that the result of t-test (2,296) was higher than t-table (1,711) at the significant level = 0,05 and the number of degree of freedom (df) = 24. Therefore. Based on the result of the analysis. It can be concluded that Fantasy Stories Technique  Towards Students’ Creativity in Writing at the Second Grade Students’of  SMAN 1 Praya Timur in academic year 2017/ 2018 is effective.